Perlindungan Hukum Terhadap Kerusakan Lingkungan dalam Konflik Bersenjata: (Legal Protection of Environmental Damage in Armed Conflict) - Tri Bowo Hersandy Febrianto; Irwan Triadi (Jurnal Hukum dan Sosial Politik, 2024)
International Humanitarian Law and International Environmental Law have paid serious attention to environmental damage resulting from armed conflict, but the legal protection efforts issued by these two laws have not yet been fully used as guidance for the parties to the conflict. This research aims to provide an overview of environmental protection arrangements in situations of armed conflict. A normative juridical method with a case approach and related conventions has been used in this research. The results of the research are that basically the regulations regarding the application of law related to legal protection of the environment in armed conflict are contained in International Humanitarian Law and International Environmental Law, so it is necessary to integrate these two laws so that they can strengthen each other and serve as guidelines for the parties. which is in conflict.